2019
DOI: 10.1002/jlcr.3818
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cytotoxicity Of Shikonin‐Silver Nanoparticles As An Opportunity For Lung Cancer

Abstract: The combined action of shikonin and silver nanoparticles (AgNPs) for apoptosis in human cancer cells has not been elucidated. Hence, we investigated the synergistic combinatorial effect of shikonin and AgNPs in human lung cancer cells. Shikonin was used as a reducing and capping agent for AgNPs synthesis as a green method avoiding the hazards of chemical methods. Radiolabeling of shikonin-AgNPs with radioactive iodine forming [ 131 I]I-Shikonin-AgNPs was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, it has already been shown for shikonin that there are ways to overcome this problem. Fayez et al [ 53 ] reported recently that a combination of shikonin and silver nanoparticles synergistically inhibited the growth of lung cancer cells. Wang et al [ 54 ] have shown that shikonin and JQ1, a bromodomain and extra-terminal motif (BET) inhibitor, encapsulated in lactoferrin nanoparticles changed the tumor immune microenvironment, activated immunogenic cell death, repolarized protumor phenotype, tumor-associated macrophages, and repressed glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has already been shown for shikonin that there are ways to overcome this problem. Fayez et al [ 53 ] reported recently that a combination of shikonin and silver nanoparticles synergistically inhibited the growth of lung cancer cells. Wang et al [ 54 ] have shown that shikonin and JQ1, a bromodomain and extra-terminal motif (BET) inhibitor, encapsulated in lactoferrin nanoparticles changed the tumor immune microenvironment, activated immunogenic cell death, repolarized protumor phenotype, tumor-associated macrophages, and repressed glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…With the advancement of science and technology, researchers from all over the world have been focusing on the synergistic detoxification effects of potent drug molecules in combination or association with other components such as drug-metal nanoparticles, drug-carbon dots, and drug-related derivatives. These types of synergistic detoxification methodologies have emerged rapidly in recent years, particularly in cancer and other deteriorative ailments' treatment Advancement in cancer treatment studies show the potential of shikonin-AgNPs (silver nanoparticles) nanoparticles against A549 cells (human lung carcinoma cell line) (Fayez et al, 2020). Shikonin used in the synthesis of AgNPs reduced the hazards related to toxic chemicals, and together they possess inhibitory and proliferation activity against A549 cells (Fayez et al, 2020).…”
Section: Antitumoral and Anti-cancer Effectsmentioning
confidence: 99%
“…These types of synergistic detoxification methodologies have emerged rapidly in recent years, particularly in cancer and other deteriorative ailments' treatment Advancement in cancer treatment studies show the potential of shikonin-AgNPs (silver nanoparticles) nanoparticles against A549 cells (human lung carcinoma cell line) (Fayez et al, 2020). Shikonin used in the synthesis of AgNPs reduced the hazards related to toxic chemicals, and together they possess inhibitory and proliferation activity against A549 cells (Fayez et al, 2020). The IC50 of shikonin-AgNPs determined by MTT assay after 24 h was 2.4 ± 0.11 μg/ml (Fayez et al, 2020).…”
Section: Antitumoral and Anti-cancer Effectsmentioning
confidence: 99%
“…Through radioiodination of 131 I to the synthesized shikonin-AgNPs, biodistribution studies by gamma counting showed their highest preferential retention time in the lung tissues at all-time points compared to other organs, indicating specific targeting in lungs. Moreover, shikonin-AgNPs also showed inhibitory effects for A549 cells in cell viability and proliferation [37]. AuNPs were used as delivery cargos to deliver boron atoms to cancer cells for boron neutron capture therapy (BNCT).…”
Section: Nanomaterials For Theranostic Nuclear Imaging Probesmentioning
confidence: 99%